(untitled) (Tribhuvan University Journal of Food Science and Technology, 2024)
Tempeh, a traditional Indonesian fermented soybean product, derives its characteristic texture, flavor, and enhanced nutritional properties from the metabolic activity of the filamentous fungus Rhizopus oligosporus. This study aimed to isolate and identify R. oligosporus from fresh Hibiscus leaves collected in Dharan, Nepal, for application in tempeh production and evaluation of antibacterial activity. Fungal isolation from leaf samples was carried out using Potato Dextrose Agar (PDA). Identification was based on macroscopic colony morphology and microscopic characteristics. The isolate was further evaluated for growth at different temperatures (4°C, 20°C, 30°C, and 37°C) to determine optimal conditions. Tempeh was prepared by inoculating cooked soybeans with a spore suspension (106 spores/ml) of R. oligosporus and incubating at 30 ± 2°C for 36-48 h. Fermentation efficiency was enhanced by supplementing soybeans with flours from potato, maize, wheat, and rice at concentrations ranging from 0.5% to 2%. Antibacterial activity of fresh tempeh extract was assessed against Staphylococcus aureus and Escherichia coli using a membrane-sterilized (0.45 μm) filtrate. Out of 30 samples, 4 isolates (13%) were identified as R. oligosporus based on morphological and microscopic features. The selected strain exhibited optimal growth at 37°C and effectively fermented soybeans into compact tempeh. Supplementation studies indicated that 1% potato starch and 0.5% rice flour produced superior tempeh quality. The tempeh extract demonstrated inhibitory activity against S. aureus but not E. coli. These findings suggest that Hibiscus leaves may serve as a sustainable local source of R. oligosporus, supporting cost-effective, regionally adapted starter culture development and functional food production in Nepal.